Os limites do discurso da igualdade racial no Brasil - Machado, Fabiano Duarte (2009)
This paper aims to point out the limits of the discourse of equality and racial democracy in Brazil developed by the government of President Luiz Inácio Lula da Silva as well as his opponents of affirmative action policies which in his criticism recover the memory of democracy of races in Brazil, trying to put an end to all contradictions of Brazil s historical formation. To develop this analysis we set out from the particularities of the State in Brazil, from the classical concepts, developing the construction of Brazil as a nation and its educational project over the centuries. The formation of black identity has also been processed from the theoretical influences of the abolitionist process to fully develop the conditions of production of the discourse of racial democracy. To develop our analysis we use the theoretical and methodological framework of its discourse analysis. Through the categories of production conditions, ideological formation, discursive formation, memory, implicit and silencing, we show from the speech of the government and its opponents the limits of such policies.